2014
DOI: 10.1007/s40520-014-0250-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Qigong on quality of life, pain and depressive symptoms in older adults admitted to an intermediate care rehabilitation unit: a randomized controlled trial

Abstract: According to our results, a structured Qigong intervention, together with usual care, might contribute to improve quality of life of patients admitted to a post-acute intermediate care rehabilitation unit, compared to usual care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 12 publications
1
16
0
1
Order By: Relevance
“…Also, sociocultural factors such as familismo and group identity that are attributed to the Latino community [40] may have resulted in improvements in their psychosocial status following participation in the Tai Chi program. Hence, in keeping with previous research [20,25,39], we hypothesize that these positive psychosocial benefits may have contributed to their improved functional status at the end of the program. Further research is needed to explore the relationship between changes in psychosocial status and its impact on functional ability following a Tai Chi exercise program.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Also, sociocultural factors such as familismo and group identity that are attributed to the Latino community [40] may have resulted in improvements in their psychosocial status following participation in the Tai Chi program. Hence, in keeping with previous research [20,25,39], we hypothesize that these positive psychosocial benefits may have contributed to their improved functional status at the end of the program. Further research is needed to explore the relationship between changes in psychosocial status and its impact on functional ability following a Tai Chi exercise program.…”
Section: Discussionsupporting
confidence: 76%
“…For example, a Finnish study by Rantakokko et al [38] showed that older people with minor depressive symptoms at baseline experienced a decrease in depression following a 3-month outdoor activity intervention. In a randomized controlled study, the depression and quality of life improved after a structured Qigong intervention in non-Latinos [39].…”
Section: Discussionmentioning
confidence: 99%
“…Effects of Qigong practice on electrocardiographic parameters (Lee et al, 2000 , 2003 ), blood pressure (Lee et al, 2003 ; Cheung et al, 2005 ), and breathing frequency (Sun, 1988 ) were investigated. Positive effects of Qigong practice on mental health were shown in anxiety disorders (Lee et al, 2004 ; Abbott and Lavretsky, 2013 ; Chan et al, 2013 ), posttraumatic stress disorders (Grodin et al, 2008 ; Kim et al, 2013 ), major depression (Tsang et al, 2003 ; Wang C. W. et al, 2013 ; Wang F. et al, 2013 ; Yeung et al, 2013 ; Yin and Dishman, 2014 ; Liu et al, 2015 ; Martínez et al, 2015 ), in the burnout syndrome (Stenlund et al, 2009 , 2012 ), and in tinnitus (Biesinger et al, 2010 ). In recent studies, a stress alleviating effect was shown in healthy practitioners (Posadzki et al, 2010 ; Terjestam et al, 2010 ; Glei et al, 2012 ; Sousa et al, 2012 ; Hwang et al, 2013 ; Shim, 2014 ; Wang et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…A total of 15 of 25 participants in the qigong group (60%) reported that they conducted qigong treatment five times or more per week, even though they had this treatment more than 42 times for 12 weeks. Our compliance rate was low compared with clinical trials that used medication with a rate of 83–94% [26], as well as a previous study on qigong that showed adherence of 79% of participants [27]. Another previous study on qigong for breast cancer also reported a compliance of 89.6% in participants who had group qigong sessions and 78.5% for home qigong exercise [28].…”
Section: Discussionmentioning
confidence: 69%